Analysing Reading Skill in National Plus School Curriculum: Phonological Awareness of Young Learners - Ariati, Jumerli (REiLA : Journal of Research and Innovation in Language, 2020)
This research aims to analyse reading skill of English for young learners in SES national plus school which teaches their classes using full Indonesian or full English. The researcher used phonological awareness test to determine the students’ ability to switch between the two languages. 63 young learners from the selected school were tested to find out the nature of their awareness when it comes to the reading tasks. This study used central tendency measures of descriptive statistics to summarise and describe the data. The results indicate that the respondents displayed phonological awareness in some tasks and experienced difficulties in other tasks. Various deficits in phonological awareness of the bilingually educated young learners were observed and categorised as Initial Sound Identification, Final Sound Detection, Final Sound Detection and Letter Identification